Synthesis and Crystal Structure of Ammonium, Strontium Hexacyanoferrate(II) Dihydrate - Medina Córdoba, L. (2011)
The molecular structure of Sr(NH₄)₂[Fe(CN)₆]·2H₂O, was determined by X-ray diffraction methods. It crystallizes in the orthorhombic Pnma space group with a = 13.1420(3), b = 14.1656(4), c = 7.3364(2) Å, and Z = 4. The structure was solved and refined. The iron(II) complex is located on a crystallographic inversion center with the metal in a nearly perfect octahedral environment [Fe–C bond distances from 1.919(4) to 1.939(4) Å]. The Sr(II) ion lies on a crystallographic mirror plane, sandwiched between two nearly square Archimedean anti-prism basis, angled 45º from each other. One base is formed by the two water molecules located on the mirror plane [Sr···Ow distances of 2.741(4) and 2.636(4) Å] and by a pair of mirror-related cyanide N-atom [d(Sr···N) = 2.676(3) Å], the other one by two pairs of mirror-related cyanide nitrogen atoms [Sr···N distances of 2.649(3) and 2.640(4) Å] of neighboring [Fe(CN)₆]⁴⁻ anions. The infrared absorption spectrum of the compound was also recorded and briefly discussed. The paper reports the synthesis and molecular structure of the new complex hexacyanoferrate (II) of ammonium and strontium dihydrate. It crystallizes in the orthorhombic Pnma space group with a = 13.1420(3), b = 14.1656(4), c = 7.3364(2) Å, and Z = 4.